Aggregation kinetics of UV irradiated nanoplastics in aquatic environments. (15th October 2019) - Liu, Yanjun; Hu, Yiben; Yang, Chen; Chen, Chengyu; Huang, Weilin; Dang, Zhi
Abstract: Nanoplastics (NPs) derived from degradation of macroplastics and microplastics possess potential threat to aquatic biota and human health. Their fate and transport in aquatic systems are mainly governed by aging processes and aggregation behavior. In this study, we simulated plastic aging process using UV-irradiation and compared the aggregation kinetics of fresh versus aged polystyrene NPs (PSNPs) under aqueous conditions. The results showed that fresh PSNPs had strong negative surface charge and exhibited both reaction- and diffusion-limited aggregation regimes, in agreement with classic Derjaguin−Landau−Verwey−Overbeek (DLVO) theory. Divalent electrolytes were 10–15 times more effective in inducing PSNP aggregation than monovalent electrolytes. The aging process inhibited PSNP aggregation in NaCl solutions by increasing the negative charge on PSNP surface and the organic matter content in solution, while promoted PSNP aggregation in CaCl2 solutions due to interactions between Ca 2+ and carboxyl groups formed on aged PSNP surface. Such distinct behaviors were consistent with characterizations by contact angle measurements, potentiometric titration, total organic carbon (TOC) analysis, Fourier Transform Infrared Spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). Hamaker constants obtained from DLVO fitting decreased from 3.5 × 10 −21 J for fresh PSNPs to 1.5 × 10 −21 J for aged PSNPs. This study indicated that UV-irradiation plays a vital role in governing the fate, transport, and potential hazards of PSNPs in aquatic environments. Graphical abstract: Image 1 Highlights: Effects of UV-irradiation on characteristics and aggregation of PSNPs were studied. Aggregation behaviors of both fresh and UV-irradiated PSNPs follow the DLVO theory. UV-irradiation inhibits PSNP aggregation in NaCl but promotes it in CaCl2 solutions. Hamaker constants of PSNPs decrease from 3.5 to 1.5 × 10 −21 J after 24 h irradiation. Irradiated PSNPs undergo structural change and form O-containing functional groups.